ANALISIS FAKTOR KINERJA KADER DALAM PENEMUAN KASUS TUBERKULOSIS (TB) PARU DI KOMUNITAS PENABULU-STPI KABUPATEN TANGERANG TAHUN 2022 - Wulandari, (2022)
The gap between estimation and case finding of Pulmonary Tuberculosis in Tangerang could hinder the achievement of the TB elimination program in 2030. Support from all levels of society is needed to overcome this problem. The Penabulu-STPI community in Tangerang is a consortium that works with cadres in TB control, but in its implementation there are only 47% of active cadres and the case finding target set by the Penabulu-STPI community in Tangerang Regency has not been achieved. This study aims to analyze the factors related to the performance of cadres in finding cases of pulmonary tuberculosis in the Penabulu Community-STPI Tangerang. This research method is quantitative with a cross sectional approach. The results showed that the length of work (p=0.045), compensation (p=0.003) and leadership (p=0.021) had a significant relationship with the performance of cadres in finding cases of pulmonary TB. However, there was no relationship between age (p=0,347), education (p=0,324), workload (p=1,000) and work stress (p=0,593) with cadre performance in finding cases of pulmonary TB. The Penabulu-STPI community is expected to continue to monitor and evaluate the performance of cadres and then find solutions to the obstacles felt by cadres while on duty and maximize compensation to increase cadres' motivation and performance.